Sequential 1, 4‐/1, 2‐Addition of Lithium(trimethylsilyl)diazomethane onto Cyclic Enones to Induce C−C Fragmentation and N−Li Insertion. (22nd December 2015) - O'Connor, Matthew J.; Sun, Chunrui; Guan, Xinyu; Sabbasani, Venkata R.; Lee, Daesung
Abstract: α, β‐Unsaturated ketones generally undergo addition reactions with nucleophiles with a preference for either 1, 2‐ or 1, 4‐addition, but rarely both. However, the right combination of reagents allows for consecutive 1, 4‐ and 1, 2‐additions to occur: Cyclic α, β‐unsaturated ketones undergo double additions with lithium(trimethylsilyl)diazomethane, effectively generating various molecular frameworks with complexity and diversity. Owing to the sequential generation of several intermediates of multifaceted reactivity, including diazoalkane derivatives and alkylidene carbenes, it is possible to induce novel Grob‐type C−C fragmentations, alkylidene carbene mediated Li−N insertions, and dipolar cycloadditions by controlling the reaction parameters.